Politeness in Language in Student Discussions at Akprind University Indonesia - saudah, siti; Ambawani, Suprih; Eko Putranti, Bernadetta (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Language politeness is a very important aspect in shaping students' language and character. Therefore, it is necessary to pay attention to aspects of politeness in language, so it is necessary to analyze any deviations and comply with the principles of politeness in language in discussions in the classroom. The method used in this research is a qualitative descriptive method. Data collection techniques use proficient free-involved listening techniques and note-taking techniques. Data analysis uses the practical equivalent method. Determining deviations and compliance with the principles of language politeness is based on indicators of language politeness with Leech's theory. The research results show that: 1) The maxims that are often violated in learning using the discussion method are: the maxim of generosity, the maxim of humility, and the maxim of agreement. 2) The maxim of that do not appear in learning using the discussion method are: the maxim of wisdom, the maxim of acceptance, and the maxim of sympathy. 3) The use of language in learning using the discussion method often uses inappropriate diction/word choices. 4) Language politeness in learning using the discussion method has not been fulfilled properly